DSP Based Sensorless Control Of A BLDC Motor With Direct Back EMF Detection Method. - Nagadeven, Nagadeven; Taib, Soib; Rama Rao, K. S. (2007)

(untitled)
This paper proposes a scheme for sensorless control of brushless dc (BLDC) motor by a direct back EMF detection method.